Discourse Information Grammar and Explanatory Adequacy - Sevigny, Alexandre (Linguistica Atlantica, 2004)
This paper examines the concept of explanatory adequacy and addresses some of the problems triggered by rapid theoretical paradigm shifts that occurred in linguistics in the twentieth century. Concurrently, it also examines and comments on some of the difficulties which have inevitably arisen due to a noisy terminological landscape that makes it difficult to formulate, let alone evaluate, theories and hypotheses for their explanatory force. A concept of languaging is introduced which encompasses the information-based approach to linguistics that underlies Discourse Information Grammar, a cognitive pragmaticallybased and usage-based approach to the scientific study of language and cognition.